Preclinical models of congestive heart failure, advantages, and limitations for application in clinical practice - Saura, Marta; Zamorano, Jose Luis; Zaragoza, Carlos (Frontiers in Physiology, 2022)
Congestive heart failure (CHF) has increased over the years, in part because of recent progress in the management of chronic diseases, thus contributing to the maintenance of an increasingly aging population. CHF represents an unresolved health problem and therefore the establishment of animal models that recapitulates the complexity of CHF will become a critical element to be addressed, representing a serious challenge given the complexity of the pathogenesis of CHF itself, which is further compounded by methodological biases that depend on the animal species in use. Animal models of CHF have been developed in many different species, with different surgical procedures, all with promising results but, for the moment, unable to fully recapitulate the human disease. Large animal models often provide a more promising reality, with all the difficulties that their use entails, and which limit their performance to fewer laboratories, the costly of animal housing, animal handling, specialized facilities, skilled methodological training, and reproducibility as another important limiting factor when considering a valid animal model versus potentially better performing alternatives. In this review we will discuss the different animal models of CHF, their advantages and, above all, the limitations of each procedure with respect to effectiveness of results in terms of clinical application.